Introduction to Harmonic Analysis on Reductive P-adic Groups. (MN-23) : Based on lectures by Harish-Chandra at The Institute for Advanced Study, 1971-73 - Silberger, Allan J. (Book collections on Project MUSE., 1979)
Based on a series of lectures given by Harish-Chandra at the Institute for Advanced Study in 1971-1973, this book provides an introduction to the theory of harmonic analysis on reductive p-adic groups. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.